HUBUNGAN PENERAPAN MANAJEMEN PUSKESMAS DAN KOMITMEN KERJA DENGAN MUTU PELAYANAN DI PUSKESMAS - sutaip sutaip; Adi Irwansyah (Journal of Midwifery and Health Administration Research, 2023)
Background: The quality of service at puskesmas is often a public complaint. The usual impact on the quality of puskesmas services is the dissatisfaction of paien. This study aims to determine the relationship between the implementation of puskesmas management and work commitment with the quality of service at the Bulakamba puskesmas, Brebes regency. Method: This type of research is descriptive analytic with a cross sectional design. The population of this study was 962 people in the working area of the Buakamba Health Center, with a research sample of 87 respondents using random sampling. The analysis used is univariate analysis and bivariate bivariate analysis with Chi square test There is a significant relationship between the implementation of puskesmas management and work commitment with the quality of service at the Bulakamba health center, shown by the results of the chi-square test obtained a value of (p-value) = 0.001 which is smaller than the value of α=0.05 and (p-value) = 0.001 which is smaller than the value of α=0.05. Conclusion: The conclusion in this study is that there is a relationship between the implementation of puskesmas management and work commitment with service quality. Efforts are needed by the puskesmas and health office to increase work commitment through increased rewards, career development, improved skills and good communication.